(untitled) (CIPEEX, 2025)
Digital reading, driven by technological innovations, is redefining how we consume and interact with information and literature. With the advancement of devices such as e-readers, smartphones, and tablets, along with the development of specialized reading software, access to books, articles, and publications has never been easier or more accessible. This shift reflects a significant cultural change, where technology has played a central role in creating new forms of reading and expanding the possibilities for learning and entertainment. Another aspect of digital reading is the ability to personalize the experience. Unlike physical books, e-books allow for adjustments in font size, line spacing, and even background color, making reading more comfortable and inclusive for people with visual impairments or specific preferences. Night mode, for instance, reduces eye strain by enabling reading in low-light environments, while contrast adjustments make reading easier for people with conditions such as dyslexia. Moreover, Artificial Intelligence (AI) technologies are increasingly present in digital reading platforms. Through algorithms, these systems can suggest books and articles based on user interests, creating a personalized and immersive experience. AI is also being used to convert written texts into audio and vice versa, allowing readers to choose the format that best suits their lifestyle and preferences. In the field of education, digital reading has proven to be a valuable tool. Distance learning platforms (EAD) and interactive digital books are transforming the learning process, offering students access to a vast array of educational materials. The use of hyperlinks, videos, and infographics within e-books enhances understanding and makes learning more dynamic and engaging. Research suggests that, when well-designed, these resources can improve knowledge retention and promote active learning, encouraging students to engage with the material in deeper ways. Finally, digital reading also raises questions about the future of traditional paper-based reading. While printed books remain cherished by many readers, especially for their aesthetic and sensory value, the advantages of technology—such as portability, space efficiency, and sustainability (by eliminating the need for paper)—make digital reading an increasingly attractive option. Additionally, the relationship between digital reading and technology is not merely a matter of convenience but of transformation. Technology is not only changing the medium through which we read but also how we understand, interact with, and connect to content.